2016
DOI: 10.4103/1735-1995.181993
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pyloromyotomy, pyloric buginage, and intact pylorus on gastric drainage in gastric pull-up surgery after esophagectomy

Abstract: Background:There are controversies regarding the usefulness of the pyloric drainage methods after esophagectomy as well as differences among various pyloric drainage techniques. Therefore, we compared the outcome of pyloromyotomy, pylorus buginage, and no intervention methods on gastric emptying among patients undergone esophagectomy.Materials and Methods:In this randomized clinical trial, patients with diagnosed esophageal cancer or any other benign lesions candidate for esophagectomy were selected. They rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In a recent randomized clinical trial, Mohajeri et al found that pyloromyotomy or pylorus buginage could not reduce the incidence of DGE after esophagectomy with gastric pull-up [ 24 ]. Moreover, there is evidence that patients who undergo pyloric drainage procedures may suffer from increased biliary reflux and dumping syndrome long term [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent randomized clinical trial, Mohajeri et al found that pyloromyotomy or pylorus buginage could not reduce the incidence of DGE after esophagectomy with gastric pull-up [ 24 ]. Moreover, there is evidence that patients who undergo pyloric drainage procedures may suffer from increased biliary reflux and dumping syndrome long term [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%